Malik Bennabi and the Intellectual Problems of the Muslim Ummah (American Journal of Islam and Society, 1992)
In the last several decades, Muslim and non-Muslim scholars havestudied the causes of the Muslim ummah‘s decline. As thes scholars havedifferent frames of reference and different political and cultural orientations,each group tends to view the issue according to its own understanding.However, the outcome of these studies are marred by major methadologicaldefects that have made it impossible for the authors to move beyond a merecategorization of the multiple symptoms of that malady.Most non-Muslim scholars ascribe the Muslim world’s backwatdness toIslam. Such a conclusion mflects the confmntational stand of the West towardsthe Muslim world. Although the numerous writings on the subject havebeen called ”scientific” and "academic,” in reality they are mostly defensiveand far fmm truly objective.’Muslim thinkers and reformers, while admitting the fact of the ummah’sdisintegration, have reached a different conclusion: Muslims, not Islam, haveto change? Questions as to how and why this change should take place, aswell as to who should undertake it, have remained largely incomplete andinconclusive for a variety of political and cultural circumstances. One majorweakness was that most of the studies were descriptive, as opposed to analytical,in nature. If there were any analysis at all, it was mainly theoretical andsuperficial. The lack of freedom on different levels also interfered with ...